Tahap pengetahuan nilai-nilai murni bagi memupuk keharmonian dalam kalangan belia pelbagai etnik di Selangor - Ab. Halim, Adlina; Muhammad, Zarina; Lee, Yok Fee; Tun Ismail, Wan Nor Azilawanie (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Malaysia is a country of diverse races, religions, and customs where it is known as a society which concerned about moral values towards achieving unity of the nation. Younger generation are the nation assets and they should be inculcated with noble values in order to form a civilized society with ethics and moral values. Therefore, this study aims to identify the level of knowledge among multi-ethnic youth toward the inculcation of moral values. The research design for this study is quantitative research and survey method was employed by distributing questionnaires. The study was conducted in four districts (Gombak, Ulu Langat, Petaling and Klang) in Selangor. A total number of 400 youth were selected randomly for this study. Each district comprised 100 youth from different ethnic including Malay, Chinese and Indian and age category among respondent is from 15 to 25 years. Findings of this study shows that the respondents have a high level of knowledge of the noble values which was instilled in Malaysian society. Thus, these noble values need to be understood and practiced by all people regardless of ethnicity to create harmony and social cohesion between the various ethnic groups in Malaysia.